Effect of Hydrogen Peroxide (H2O2) on Mineralization of Methyldiethanolamine (MDEA) using UV/H2O2 - S., Harimurti (2010)
Methyldiethanolamine (MDEA) in aqueous solutions are commonly used for scrubbing of carbon dioxide from natural gas. Huge quantities of MDEA appear in the wastewater during cleaning and maintenance as well as shutdown of the absorption and desorption columns. The MDEA are not readily biodegradable and such wastewater cannot be treated in the conventional treatment facility. Advanced Oxidation Processes (AOP’s), such as oxidation by Fenton’s reagent, UV/H2O2 and UV/Ozone offer a class of techniques of treatment or partial degradation of refractory organics which are not readily agreeable to conventional biological oxidation. A laboratory set up was conducted to study critical parameters of the MDEA mineralization under UV/H2O2 for efficient reduction of total organic carbon (TOC). The experiment was carried out in a glass jacketed reactor and equipped with low pressure UV lamp. The effect of UV dose and hydrogen peroxide concentration was determined. The results showed that the UV dose and initial H2O2 concentration have strong influence in the TOC removal. The highest degradation of MDEA using UV/H2O2 in this experiment was 67.05% TOC removal under 8 watt UV lamp, 2000 ppm initial MDEA concentration, and 1.5 times theoretical amount of H2O2 needed for 240 minute irradiation time.